THE PRODUCTION OF ADJACENCY PAIRS AND PREFERENCE ORGANIZATION BY SECOND YEARS STUDENTS OF MAN 1 PEKANBARU - Sonnevil, Gianini Sonnevil; Maria, Desri Maria; ', Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This descriptive research discusses conversation analysis among senior high school students. It was conducted based on the importance of adjacency pairs and preference organization in speaking; these two aspects covered the appropriateness between preceding and proceeding talk, the pattern of preferred and dispreferred response. The participants of this research was second years students of MAN 1 Pekanbaru. The data was collected by giving topics to peer of student and recorded by the researcher. Then, the recording was transcribed based on Gail Jefferson’s transcription. The research was analyzed by considering three aspects (1) the type and adequacy of students’ initiating and responding,(2) student’s ability in constructing 4 types of adjacency pairs; Question-Answer, Greeting-greeting, Telling-acceptance and invitation-refusal or acceptance,(3) preference organization: preference for agreement and preference for contiguity. Based on the data analysis, 86 % students produced Question-answer, 7.3 % of students produced Greeting-greeting, 5 % of students produced Telling-acceptance and 2 % produced invitation-acceptance or refusal. Based on the students’ ability in producing preference organizations, 83 % of students gave positive response and 4.2 % gave negative to positive question while students gave 3.3 % positive responses and 4.2 % negative response to negative question. Based on the adequacy of students’ response 21.6 % of students gave adequate plus response, 69.1 % gave adequate response, 5.8 % gave inadequate response and 0.16 % gave ambiguous response. There was also tendency that students produced more transactional question rather than interactional questions. Keyword: conversation analysis, adjacency pairs, preference organization. Students’ Speaking Ability, descriptive Research